GRAPHIC DESIGN INNOVATION AS BRAND IDENTITY FOR “MAHLZEIT N’DAS BROT” BREAD PACKAGING - Zulkarnain Zulkarnain; Deny Dwi Lestari; M. Syamsul Ma'arif (Universitas Mercu Buana, 2015)
Besides being useful for protecting food, packaging design also serves as a media campaign. So hopefully, Mahlzeit Bread n 'Das Brot can compete with other bakers and even can be a pioneer as an authentic German bread maker in Indonesia. This research was conducted by collecting information from the client (Mahlzeit n 'Das Brot owner). This information was used to obtain a verbal brand identity, then translated visually. The use of illustrations also becomes the most important visual images to present the image of Germany Elegant Vintage and privilege in explaining the products of Mahlzeit n 'Das Brot. The colors used are natural colors and traditionally the colors brown and green to indicate an authentic image of Mahlzeit n 'Das Brot.